Analysis Of The Influence Of E-Word Of Mouth, Brand Image And E-Service Quality On Repurchase Intention Of Digital Bank Customers - Donny Dharmawan; Loso Judijanto; Nurlaili Rahmi; Abdurohim; Luckhy Natalia Anastasye Lotte (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
It is feasible to switch from traditional banks to digital banks by keeping up with the trends. Using brand image as an intervening variable, this study examines the impact of e-word-of-mouth and e-service quality on repurchase intention. Purposive sampling, a nonprobability sampling approach, was employed to select the sample size, which consisted of 100 respondents who resided in some big cities in Indonesia and had used service of the bank. The respondents were contacted by Google Form. Using the SmartPLS Software program, partial least squares were used to evaluate the questionnaire responses. The findings demonstrated that while e-word-of-mouth and e-service quality have an impact on repurchase intention, they have no direct effect on brand image. Additionally, although e-service quality directly influences repurchase intention through brand image, e-word of mouth has no direct effect on this trait.